Raci Matrix and BPMN Analysis in Academic Administration: A Case Study - Fardhoni Fardhoni (Journal of Innovative and Creativity, 2025)
In the academic environment of higher education institutions, the learning administration process is one of the crucial aspects that supports the smooth running of academic activities and educational quality. This research focuses on the analysis and implementation of the RACI Matrix and Business Process Model and Notation (BPMN) in the academic administration of higher education institutions, particularly in the process of creating Study Plan Cards (KRS) at Mahardika Institute of Technology and Health Cirebon. Through this case study, the research aims to identify and map responsibilities and workflow involved in the KRS creation process, thereby improving the efficiency and effectiveness of academic administration. This research adopts a qualitative design with a case study approach, where data is collected through observation, document analysis, and the use of diagrams.net tools for BPMN creation. The results of this research indicate that the implementation of RACI Matrix and BPMN can provide clear guidance on the roles and responsibilities of each party, as well as facilitate understanding of the KRS creation process flow. This has the potential to enhance coordination and communication among involved parties, and reduce errors and ambiguities in the academic administration process.